Adaptive Channel Estimation Using Frequency-Response-Shaped LMS Algorithm in DS-CDMA Systems - Ahmad, Mohammad Shukri; Hocanin, Aykut; Kuekrer, Osman (IEEE, 2008)
An adaptive least mean square (LMS) type channel estimation algorithm is proposed. The proposed algorithm employs the Frequency-Response-Shaped Least Mean Square (FRS-LMS) algorithm which outperforms the LMS and the Modified Leaky LMS algorithms in a fading channel with correlated Gaussian noise. The algorithm is based on shaping the frequency response of the transversal filter by inclusion of a leakage factor in matrix form. The FRS-LMS algorithm converges to a lower MSE compared with the Modified Leaky LMS in correlated Gaussian noise leading to a substantial decrease in bit error rate for Direct Sequence Code Division Multiple Access (DS-CDMA) systems. In a fading channel with AWGN, the proposed algorithm has a lower performance gain relative to the Modified Leaky LMS algorithm bid provides a significant performance advantage over the standard LMS algorithm. of the system.
IEEE 16th Signal Processing and Communications Applications Conference -- APR 20-22, 2008 -- Aydin, TURKEY
Keywords: Fading Channels; Modulation; Filter